Analysis of The Impact of Agricultural Land Conversion Towards Food Security in The Special Region of Yogyakarta Province - Karima Sustyaningrum; Arsanti, Vidyana; Sidiq Arfianto; Meliyani, Siti (Pusat Penelitian dan Pengabdian kepada Masyarakat, Sekolah Tinggi Pertanahan Nasional, 2024)
Abstract: The Special Region of Yogyakarta is known as a student city, a tourist destination, a place to work, and a place to live. Population growth and rising living standards have driven land demand for housing and economic activities, forcing land conversion. The shift from agricultural to non-agricultural land use has significant impacts, particularly on food supply in the region. This research aims to analyze the effect of agricultural land area on food security in Yogyakarta. The method used includes Supervised Classification analysis to determine the distribution and rate of land conversion, and correlation analysis to assess the cost of food security. The results show that wetland conversion has led to a loss of rice production in Yogyakarta amounting to 13,726 tons per year, or 123,534.73 tons over the past nine years. However, food security in the region remains unaffected despite the conversion of wetland areas. Keywords: Agricultural land conversion, Food availability, Food security, Supervised Classification